Challenges in Measuring Outcomes Following Digital Replantation - Sebastin, Sandeep J.; Chung, Kevin C. (Seminars in Plastic Surgery, 2013)
In the early period of replantation surgery, the emphasis was on digit survival. Subsequently, with better microsurgical techniques and instrumentation, the focus has shifted to function and in recent years to consideration of cost-effectiveness. Despite over 40 years of effort in refining digital replantation surgery, a rigorous evaluation of the outcomes of digital replantation has not been performed. This is because of the many confounding variables that influence outcome comparisons. These variables include the mechanism of injury (guillotine, crush, avulsion), the injury itself (total, near total, subtotal, partial amputation), and the surgical procedure (replantation, revascularization). In addition, the traditional outcome measures (two-point discrimination, range of motion, grip strength, or the ability to return to work) are reported inconsistently and vary widely among publications. All these factors make meaningful comparison of outcomes difficult. The recent emphasis on outcome research and cost-effectiveness necessitates a rethinking in the way we report outcomes of digital replantation. In this article, the authors summarize the challenges in assessing outcomes of digital replantation and explain the need to measure outcomes using rigorous clinical research designs that incorporate cost-effectiveness studies in the research protocol.
Keywords: digital replantation; outcome of replantation; research design; health-related quality of life instruments; cost effectiveness